A Thyroid Carcinoma Induced by COVID-19 and its Effect on The Variation of Thyroglobulin Level as a Marker for Diagnosis and Assessment Strategy - Kudhair, Ahmed Hassan; Almahbobi, Taghreed F.; Jawad, Anfal Abdulhussain; Baqer, Enas Jalil; Kadhim, Dhuha Abdullah; Al-Mayaly, Adel Sahib; Abbas, Hanan Diekan (Medical Science Journal for Advance Research, 2024)
Background: the thyroid carcinoma is one of the most cases seen of the thyroid un expected disease. Due to its increase in the no of cases reported there is un urgent interest of the prognostic risk expectations and the out come of the treatment. there will be an increment of the cases and an interesting in prohibit its complications by follow-up this disease. Aim: is to predict the effect of the thymoglobulin test in facilitating its diagnosis in consideration with selectivity and the specify. Results: data indicated that although this test is helpful in the diagnosis but still it is not only deoendable test used due to lack of complete accuracy in different cases of the thyroid disease. one of the main reasons for the thyroid carcinoma is viral infection, particularly COVID due its effect on the endocrine function of the human body especially thyroid gland and its abnormally proliferation and behavior that could be ends with tumors even if this tumor is multifactorial but there is and evedance that it caused by viral infection.